Measures to Curb Polygamy Scams in Malaysia: A Legal Perspective - Mat Zain, Mat Noor; Mahsor, Ahmad Faris Zikri; Abdul Manap, Norhoneydayatie (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The law relating to polygamy is practically weak due to the lightly punishment imposed, re-registration in the Court is allowed if the marriage is legal. This makes society more vulnerable and affected to polygamy without permission and unknowingly fall into polygamy scams. Polygamy scams are becoming increasing prevalent in Malaysia even though this phenomenon has existed for a long time. This form of marriage cannot be validated if the courts do not grant permission, procedures are not adhered to or there is an element of manipulation. This scheme occurs due to several factors, including the role of certain individuals, syndicate, and the legislation. Therefore, this qualitative study used the case study approach to explain the concept of polygamy scam and examine proactive measures aimed at curbing polygamy scams from a legal perspective. Data were collected using the content analysis and interview methods. The data were analyzed on a thematic and descriptive method. Findings indicate that a polygamy scam is a matrimonial offense that is liable to prosecution in the Syariah Courts. It was also found that there is a need for standardization, empowerment, and law enforcement at the federal and state levels. Several initiatives were suggested, such as appropriate punishment imposed on the masterminds behind the polygamy scams, complaints should be filed whenever a case arises and increasing the number of awareness programs aimed at curbing or even eradicating polygamy scam activities altogether. The implication of this study is that the governments and stakeholders need to play important role in enforcing laws on polygamous offences without permission including scam activities.